Triggers of Malaysian consumers’ impulse purchase during live streaming - Haw, Mei Kei (2023)
With the rapid growth of the e-commerce market in Malaysia and the recent popularity of live streaming sales. Correspondingly, the situation of consumers purchasing merchandise through live streaming is also increasing. Therefore, this paper aimed to identify the factors that affect Malaysian consumers to make impulse purchases during live streaming shopping. With this aim, a convenience sample of 394 Malaysian consumers who had previously experienced on live streaming shopping were collected via a self-administered questionnaire. Proposed hypotheses and data analysis were tested using the Statistics Package for Social Sciences (SPSS). Besides, the Stimulus Organism Response model was employed as a theoretical model in this study to investigate the influence of price discount, visual appeal, interactivity on consumers’ impulse purchase during live streaming as well as perceived enjoyment act as a mediator variable. The findings of this research reported that visual appeal and interactivity has a positive impact on consumer’s perceived enjoyment during live streaming. It was also revealed that perceived enjoyment and price discount inspire consumers impulse to purchase during live streaming shopping. In addition, the empirical findings also found that the perceived enjoyment plays a mediating role among visual appeal, interactivity and impulse purchase. At the end of this study, theoretical contributions, managerial implications, limitations and recommendations for future research are provided.